Pengaruh Waktu Tunggu Antrian terhadap Kepuasan dan Niat Berkunjung Kembali di Kopi Klotok Kaliurang - Hendrajaya, Agnestasya Monica Putri; Pratika, Diah Agih; Veronica, Audiea; Afif, Fuadi; Hermawan, Hary; Ghani, Yosef Abdul (LPPM STP ARS Internasional, 2025)
This study investigates the impact of waiting time on visitor satisfaction and revisit intention at Kopi Klotok, a renowned local culinary destination. Using a quantitative approach with structural equation modelling (SEM), data were collected from 150 respondents who had visited Kopi Klotok. The results show that waiting time significantly influences visitor satisfaction (? = 0.326, p < 0.001) and revisit intention (? = 0.451, p < 0.001), with satisfaction also strongly affecting revisit intention (? = 0.592, p < 0.001). These findings emphasise the importance of managing queues and providing comfort during waiting to enhance loyalty. Practical implications include implementing reservation systems, extending operating hours, and improving waiting area facilities to ensure a positive visitor experience.